To solve the equation \( \frac{2f}{5} - \frac{8}{5} + 2f = 8 \), we can follow these steps:
-
Combine like terms: First, let's write \( 2f \) in terms of fractions with a common denominator. The common denominator here is 5.
We can express \( 2f \) as \( \frac{10f}{5} \) (since \( 2f = \frac{10f}{5} \)).
Now we can rewrite the equation:
\[ \frac{2f}{5} - \frac{8}{5} + \frac{10f}{5} = 8 \]
-
Combine the fractions on the left side:
\[ \frac{2f + 10f - 8}{5} = 8 \]
This simplifies to:
\[ \frac{12f - 8}{5} = 8 \]
-
Clear the fraction: Multiply both sides by 5 to eliminate the fraction:
\[ 12f - 8 = 40 \]
-
Add 8 to both sides:
\[ 12f = 48 \]
-
Divide both sides by 12:
\[ f = 4 \]
Thus, the solution to the equation is \( f = 4 \).
The correct response is 4.